Requisitos configuradores do grupo econômico e limites a sua responsabilidade tributária - Coelho, Aline Fossati (2023)
Tax responsibility, in particular, the issue of economic group responsibility, generates different interpretations, from the local magistrate to our Superior Courts. The responsibility of companies that are part of an economic group, in the processing of executive actions and the jurisprudential innovations that allow reaching third-party assets and rights, has been used, in many cases, as a means of sanctioning and coercing the payment of tax obligations. A company of the economic group may be subject to bearing the effects of tax exactions from another, even if it is in good standing with the Tax Authorities. This is because attorneys' offices use redirection requests with a request for disregard of legal personality to extend the effects of joint and several tax liability to everyone. The purpose of the study is to assess whether there is a legal tax rule that authorizes the accountability of a member of an economic group other than the one that practiced the tax materiality. We will examine the concept of economic group, the organic structure, the legal relationship that triggers solidarity with the economic group, under the focus of the rules of the National Tax Code. Finally, we will verify if Law 8.212/1991 and article 50 of the Civil Code are compatible with the propositions of the National Tax Code and the possibility of using these legal norms in tax law, as a form of accountability of all members of the economic group. In conclusion, it is exposed that the lack of a legal rule in the National Tax Code, regulating concept and consequences to the members of the economic group, entails violation of the limits that the Constitutional legislator conferred for the election of new tax officials